2018
DOI: 10.12659/msm.912010
|View full text |Cite
|
Sign up to set email alerts
|

Tear Luminex Analysis in Dry Eye Patients

Abstract: BackgroundThe purpose of this study was to analyze tear inflammatory cytokines of different subclasses of dry eye disease (DED) patients using Luminex technology.Material/MethodsForty-five DED patients including 20 Sjogren syndrome aqueous tear deficiency (SS-ATD) patients, 20 non-Sjogren syndrome aqueous tear deficiency (NSS-ATD) patients, 15 meibomian gland dysfunction (MGD) patients, and 15 normal participants were enrolled in this study. Concentrations of 11 inflammatory cytokines in tear samples of study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 34 publications
(31 reference statements)
3
45
0
1
Order By: Relevance
“…Th1 cells have also been narrowly associated to development and disease severity, owing to their selective infiltration into target tissues, analyzed by the presence of the transcription factor T-bet and IFN-γ [ 28 ]. Alternatively, some studies have found an increased expression of predominantly Th1-cytokines, such as IL-2, IL-12, IFN-γ, and IP-10, in liquids like tears and saliva from pSS patients correlating with clinical manifestations [ 29 , 30 ]. Consistent with the underlying mechanism to shape the setting of the inflammatory and detrimental environment, IFN-γ might disrupt tight junction structure in glandular tissue from SS patients [ 31 ], indicating that the local cytokine production may contribute to the observed glandular dysfunction.…”
Section: Th1/th17 Cells: Primordial Effectors Coordinating the Infmentioning
confidence: 99%
See 1 more Smart Citation
“…Th1 cells have also been narrowly associated to development and disease severity, owing to their selective infiltration into target tissues, analyzed by the presence of the transcription factor T-bet and IFN-γ [ 28 ]. Alternatively, some studies have found an increased expression of predominantly Th1-cytokines, such as IL-2, IL-12, IFN-γ, and IP-10, in liquids like tears and saliva from pSS patients correlating with clinical manifestations [ 29 , 30 ]. Consistent with the underlying mechanism to shape the setting of the inflammatory and detrimental environment, IFN-γ might disrupt tight junction structure in glandular tissue from SS patients [ 31 ], indicating that the local cytokine production may contribute to the observed glandular dysfunction.…”
Section: Th1/th17 Cells: Primordial Effectors Coordinating the Infmentioning
confidence: 99%
“…Additionally, in the line of SS pathology-influencing Tfh factors, in vitro analysis valuing pSS patients-derived SG epithelial cells revealed that these cells promote naïve T cells differentiation into Tfh in an IL-6 and ICOL dependent manner [ 97 ]. This evidence suggests that Tfh may mature at site of inflammation, and IL-6 exhibits crucial roles for Tfh cell generation during humoral response, which would allow focusing on IL-6 as a target to downregulate Tfh cells frequency, since IL-6 is increased in SS [ 29 ]. Alternatively, Achaete-scute complex homologue 2 (Ascl2) is a novel molecule that has been reported to induce Tfh cells differentiation.…”
Section: Tfh Cell: Building the Niche Leading To Progressive Damagmentioning
confidence: 99%
“…Measurements of inflammatory mediators in the tear film help to identify the inflammatory reaction and the severity of DED [22,28,38]. The levels of various cytokines (TNF-α, IL-1α, IL-1ß, IL-6, IL-8, IL-10, IL-12P70, IL-13, MIP-1α, IFN-γ) and MMP-9 in tears of DED patients are significantly higher than those in normal people [22,28,40,41]. Statistical differences among subclasses of DED for IL-8 and TNF-α were observed and it could be significant for diagnosing and treatment of DED [40].…”
Section: -(1)mentioning
confidence: 99%
“…The levels of various cytokines (TNF-α, IL-1α, IL-1ß, IL-6, IL-8, IL-10, IL-12P70, IL-13, MIP-1α, IFN-γ) and MMP-9 in tears of DED patients are significantly higher than those in normal people [22,28,40,41]. Statistical differences among subclasses of DED for IL-8 and TNF-α were observed and it could be significant for diagnosing and treatment of DED [40]. The activity of cathepsin S (CTSS) in tears and the level of HLA-Dr in impression cytology were higher in patients with SS than in patients with non-SS DED and healthy subjects [22].…”
Section: -(1)mentioning
confidence: 99%
“…The mechanism of development of DE is still unclear, but inflammation is known to be a major cause of damage to the ocular surface and cellular damage [7]. Indeed, a clinical study reported that the levels of interleukin (IL)-1, IL-6, IL-8, and tumor necrosis factor-alpha (TNF-α) are higher in the tears of DE patient tears than in healthy individuals [8]. Thus, a substance capable of regulating inflammatory cytokines is a potentially effective therapeutic agent for DE.…”
Section: Introductionmentioning
confidence: 99%